The Coupling Between Cell Wall Integrity Mediated by MAPK Kinases and SsFkh1 Is Involved in Sclerotia Formation and Pathogenicity of Sclerotinia sclerotiorum - Cong, Jie; Xiao, Kunqin; Jiao, Wenli; Zhang, Cheng; Zhang, Xianghui; Liu, Jinliang; Zhang, Yanhua; Pan, Hongyu (Frontiers in Microbiology, 2022)
The plant pathogenic fungus Sclerotinia sclerotiorum can survive on a wide range of hosts and cause significant losses on crop yields. FKH, a forkhead-box-containing protein, functions to regulate transcription and signal transduction. As a transcription factor with multiple biological functions in eukaryotic organisms, little research has been done on the role of FKH protein in pathogenic fungi. SsFkh1 encodes a protein which has been predicted to contain forkhead-box domain in S. sclerotiorum. In this study, the deletion mutant of SsFkh1 resulted in severe defects in hyphal development, virulence, and sclerotia formation. Moreover, knockout of SsFkh1 lead to gene functional enrichment in mitogen-activated protein kinase signaling pathway in transcriptome analysis and SsFkh1 was found to be involved in the maintenance of the cell wall integrity and the mitogen-activated protein kinase signaling pathway. Yeast two-hybrid and bimolecular fluorescence complementation assays showed that SsFkh1 interacts with SsMkk1. In addition, we explored the conserved MAPK signaling pathway components, including Bck1, Mkk1, Pkc1 and Smk3 in S. sclerotiorum. ΔSsmkk1, ΔSspkc1, ΔSsbck1, and ΔSssmk3knockout mutant strains together with ΔSsmkk1com, ΔSspkc1com, ΔSsbck1com, and ΔSssmk3com complementation mutant strains were obtained. The results indicated that ΔSsmkk1, ΔSspkc1, ΔSsbck1, and ΔSssmk3 displayed similar phenotypes to ΔSsfkh1 in sclerotia formation, compound appressorium development, and pathogenicity. Taken together, SsFkh1 may be the downstream substrate of SsMkk1, and involved in sclerotia formation, compound appressorium development and pathogenicity in S. sclerotiorum.